Dynamic X-Ray Imaging and Its Role in Predicting Outcomes in Coccygectomy Patients: A Narrative Review - Mohannad W. Awwad; Musab Al Ageel; Abeer W. Awwad; Osama A. Alrehaili; Waleed Awwad (Journal of Spine Practice)
Background Chronic coccydynia is a debilitating condition often exacerbated by any activity that applies pressure to the coccygeal area. While diagnosis is primarily clinical, dynamic X-ray imaging has emerged as a valuable tool for identifying structural abnormalities like hypermobility or subluxation. For patients unresponsive to conservative treatments, coccygectomy (surgical removal of the coccyx) remains a definitive option. However, predicting surgical success remains challenging.